Normalized finite fractional differences: Computational and accuracy breakthroughs - Stanisławski, Rafał; Latawiec, Krzysztof J. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a series of new results in finite and infinite-memory modeling of discrete-time fractional differences. The introduced ?normalized finite fractional difference? is shown to properly approximate its fractional difference original, in particular in terms of the steady-state properties.
Keywords: fractional difference; Grünwald-Letnikov; difference; stability analysis; recursive computation; adaptive systems